Time-resolved aerodynamic loads on high-speed trains during running on a tunnel–bridge–tunnel infrastructure under crosswind. Issue 1 (1st January 2020) - Deng, E.; Yang, Weichao; Deng, Lu; Zhu, Zhihui; He, Xuhui; Wang, Ang
Abstract : A high-speed train will likely experience hazardous driving environments because of the transient effect of complex airflow condition when the train runs on the infrastructure scenario consisting of the tunnel–bridge–tunnel under crosswind. The evolution of aerodynamic loads and flow structure is investigated by numerical simulations. In these simulations, the arrangement of an infrastructural scenario refers to a real prototype under construction. Results indicate the flow structure and pressure distribution around a train change from a symmetrical state in the tunnel to a remarkable asymmetry state in the bridge within 0.1 s. This phenomenon causes a sharp aerodynamic shock on the train body. The coupling effect of the crosswind environment and the transformation of the train running scenario will likely affect the transient aerodynamic response. The maximum values of different aerodynamic loads exhibit time-resolved discrepancy when a train runs in ISTBT. The transient characteristics of the aerodynamic loads strengthen with the increase in wind speed but weaken with the increase in train speed. Such characteristics will likely deteriorate further if the wind direction is in the opposite direction relative to that of a moving train.